MO196: Moderate-To-Severe CKD-Associated Pruritus (CKD-AP) is Independently Associated with Worse Health-Related Quality of Life (HRQOL) Among Dialysis Patients. (3rd May 2022) - Ion Titapiccolo, Jasmine; Bellocchio, Francesco; Goethel-Paal, Berit; Eva Baró Salvador, Maria; Schofield, Michaela; Rincon Bello, Abraham; Chrisholm, Chis; Basnayake, Kolitha; Trkulja, Marjelka; Stuard, Stefano; Neri, Luca
Abstract: BACKGROUND AND AIMS: Chronic kidney disease–associated pruritus (CKD-aP) is common, yet underrecognized condition among end-stage kidney disease patients. We sought to evaluate the prevalence of CKD-aP and its impact on health-related quality of life (HRQOL) among dialysis patients across five European countries. METHOD: This is a retrospective, observational analysis of data abstracted from the EuCliD® database (European Clinical database), the clinical information system adopted in Fresenius Medical Care (FMC) outpatient dialysis facilities in several European countries. Patient-Reported Outcomes Measures (PROM) were collected as part of a continuous quality improvement program launched for the first time in all centres belonging to the Nephrocare network in France, Italy, Spain, United Kingdom and Ireland. The presence and severity of CKD-aP were documented based on information captured by both the Kidney Disease Quality of Life (KDQOL™-36) and the 5-D Itch questionnaires. HRQOL was assessed with KDQOL™-36. Clinical and demographic data have been extracted from EuCliD®. The relationship between CKD-aP and HRQOL was evaluated with generalized linear models. RESULTS: The ePROM campaign attained a large participation rate with very low attrition. Among 9974 who were actively treated in the clinics and were able to fill in a self-reported questionnaire, 8157 responded to the survey and only 1033 (11.2%) refused to participate. We enrolled 6221 patients in the present secondary analysis. The study flowchart is reported in Figure 1 . Slightly more than half of patients (52%) reported no CKD-aP, 25% mild, whereas roughly 23% reported moderate-to-severe CKD-aP. Patients reporting more severe CKD-aP had shorter dialysis vintage, higher phosphate and parathormone, and more frequently diabetes. Average KDQOL-36 scores are reported in Figure 2a . We observed a strong, graded relationship between CKD-aP severity and KDQOL-36 scores (Figure 2b ). The association was robust to adjustment for potential confounders. The quality of life penalty associated with more severe pruritus was clinically significant based on distribution based minimal clinically important difference threshold for the KDQOL-36 scales. CONCLUSION: CKD-aP was common in a large, representative sample of the dialysis population in five European countries. We observed a large, clinically important, quality of life penalty associated with CKD-aP even after adjusting for potential confounders.